Non-ferrous metalworking of the Upper Kyiv in the 10th-13th centuries - Kryzhanovskyi, Viacheslav (Revista Arheologică, 2026)
The Upper Kyiv is the oldest part of the city, where the administrative center with princely palaces, church estates, and boyar residences was located. The inhabitants of these complexes required a significant number of items made from non-ferrous metals. Between 1907 and 2013, excavations were conducted at 20 areas, where 83 specialized objects and 1363 artifacts were discovered and studied, including materials from 14 cultural layers that may have originated from nearby production structures. Among the identified features were 6 bronze casting workshops, 22 jewelry workshops, 6 smithy/locksmithy workshops, and 23 dwelling-workshops. Most of these objects date to the 12th – the beginning of the 13th century. Some of them were combined with ironmaking/ironworking and/or glassmaking/glassworking crafts. Numerous production structures formed five specialized craft centers in the Upper City, covering areas from 0.5 to 6 hectares. Within their fillings, 12 marketable metals, 503 semi-finished products, 690 casting vessels, 15 casting molds, 34 tools, and 112 examples of production waste were found. The emergence of a significant number of non-ferrous metalworking facilities in Upper Kyiv is explained by their proximity to the grand princely courts with their palace complexes, the estates of the boyar elite, the marketplace square, and religious buildings.